Microplastics in greywater from households, a residential building, and an urban city district - Sami, Mashreki; Hedström, Annelie; Kvarnström, Elisabeth; Herrmann, Inga (Luleå University of Technology, 2026)
The dataset include the occurrence and mass concentrations of microplastics (MPs) in greywater generated from single households, a residential building, and an urban city district. In addition, the retention capacity will be evaluated for the filter materials used in the treatment systems – package plants (for single households), a hybrid treatment wetland (for the residential building), and two green walls (at pilot scale in the urban city district). Finally, the present the MP mass concentrations in the effluents.

1. Study_Description: This file includes the summary of the research study, data collection and the standard analytical methods used for analyzing microplastics in greywater.
2. Microplastics_greywater: The influent and effluent mass concentrations of microplastics, volume sampled and filtered including the supplementary parameters.

Datamängden inkluderar förekomst och masskoncentrationer av mikroplaster (MP) i BDT-vatten från enskilda hushåll, ett flerbostadshus och en stadsdel. Dessutom utvärderas kvarhållningskapaciteten för de filtermaterial som används i behandlingssystemen – kompaktanläggningar (för enskilda hushåll), ett hybridkonstruerat våtmarksystem (för flerbostadshuset) samt två gröna väggar (på pilotskala i stadsdelen). Slutligen presenteras MP-masskoncentrationerna i utloppen.

1. Study_Description: Denna fil innehåller en sammanfattning av forskningsstudien, datainsamlingen och de standardiserade analysmetoder som använts för att analysera mikroplaster i BDT-vatten.

2. Microplastics_greywater: Inflödes- och utflödeskoncentrationer (masskoncentrationer) av mikroplaster, volymen som har provtagits och filtrerats samt kompletterande parametrar.
Mikroplaster i BDT-vatten från hushåll, ett bostadshus och ett stadsdistrikt
Keywords: water quality; vattenkvalitet; micro-litter; mikroskräp; greywater; gråvatten; polymers; polymerer; wetlands; våtmarker; constructed wetlands; Environmental Engineering; Naturresursteknik; Environmental Management; Miljöteknik och miljöledning; Water Treatment; Vattenbehandlingsbioteknik